Cover Picture: Evidence of Intracrystalline Mesostructured Porosity in Zeolites by Advanced Gas Sorption, Electron Tomography and Rotation Electron Diffraction (ChemCatChem 11/2014). Issue 11 (November 2014) - Garcia‐Martinez, Javier; Xiao, Changhong; Cychosz, Katie A.; Li, Kunhao; Wan, Wei; Zou, Xiaodong; Thommes, Matthias
<x xml:space="preserve">Abstract</x> The Zeolite Peacemakers The cover picture shows that a new family of materials, namely mesostructured zeolites, can bridge the gap between conventional (microporous) zeolites and surfactant‐templated (mesoporous) solids. In their Full Paper on p. 3110 ff., J. Garcia‐Martinez, X. Zou, M. Thommes and co‐workers describe how size‐tailored mesoporosity could be introduced into commercial zeolite Y crystals by a simple surfactant‐templating post‐synthetic mesostructuring process. The resulting mesoporous zeolite Y showed significantly improved product selectivity in both laboratory testing and refinery trials. A collaboration of three teams was able to characterize these materials with advanced techniques.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>